Use of LED light for Brussels sprouts postharvest conservation - Hasperué, Héctor Joaquín (2016)
Yellowing is the most evident symptom of senescence in green vegetables during postharvest storage. As chlorophyll synthesis is promoted by blue light, illumination would be a clean alternative to maintain healthier vegetables for longer. In this paper was assessed the effect of white-blue light-emitting diodes (WB LED) on outer and inner leaves (OL, IL) of Brussels sprouts during 10 d storage at 22ºC. The treated sprouts showed lower respiration rate and remained greener with a better visual quality, with more than 10 times chlorophylls than controls in OL and 1.6 times in IL towards the end of the storage period. The OL had a higher content of antioxidants (DPPH• and ABTS•⁺ assays) than the IL, and the treatment increased the AOX only in the OL. Total flavonoids content was higher in OL than IL, and about 20% higher in treated samples at day 10 of storage. The storage of Brussels sprouts under continuous low intensity WB LED was effective in delaying the senescence. The effect of the treatment was visible not only in the leaves exposed to light (OL) but also in the IL. The WB LED lighting would be useful to maintain or improve the quality of Brussels sprouts for both storage and transport.